Adult Male Replacement in Socially Monogamous Equatorial Saki Monkeys (Pithecia aequatorialis) - Di Fiore, Anthony (2007)
Sakis (genus Pithecia ) commonly live in socially monogamous groups, but data from wild populations on group dynamics and on the turnover of reproductive-age animals are rare. Here we describe the replacement of the adult male in one group of sakis in the Ecuadorian Amazon following the death of the initial resident. We use 354 h of focal behavioral data to describe differences in the spatial relationships among group members before and after the replacement and to examine changes in the rate of maleto-female grooming, aggression, scent marking and vocalization. Interactions with extragroup individuals within the group’s home range were more frequent during and after the replacement than before. The presence of such additional animals during periods of reproductive turnover may explain at least some reported observations of saki groups with more than 1 reproductive-age male or female.